Co-operation in risky environments: Evidence from Southern Ethiopia - McCarthy, N.; Kamara, A.; Kirk, M. (2003)
The semi-arid and arid rangelands of Sub-Saharan Africa are characterized by high variability and by heavy reliance of herders on access to common resources, predominantly pasture and water. In these systems, the capacity of the community to co-operate over resource management is critical and the effectiveness of management has a direct impact on exploitation rates and land allocation patterns. In this paper, we develop a model to capture the impact of climatic variability on capacity to co-operate and on resulting land use and allocation patterns, and apply the model to data collected from communities located on the Borana Plateau in southern Ethiopia. Results indicate that rainfall variability has a negative impact on stock densities, consistent with risk-averse producer behavior, but has no statistically significant impact on land allocation patterns in this marginal area. Furthermore, co-operation has a direct negative impact on stock densities and land allocated to private pastures. The results support the hypothesis that individual incentives to overgraze and encroach on common pastures can be mitigated in communities with high co-operative capacity.